Intimisierte Öffentlichkeiten: Pöbeleien, Shitstorms und Emotionen auf Facebook - Wagner, Elke (transcript, 2019)
In times of the internet, privacy and the public are subjected to profound changes: While privacy is considered to be increasingly at risk and controlled, the bourgeois public is visibly changing on the internet – profanities, shit storms or candy storms have partly replaced the rational discourse. Specific writing practices and systems of symbols (emoticons, memes) have transformed communication practices. Focusing on the current debate, Elke Wagner analyzes the newly created intimate public in the social web.